A technomorphic conceptualisation of biological ‘constructions’ and their evolution - Manfred Drack; Oliver Betz (Vertebrate Zoology, 2022)
Here, we build on earlier work concerning notions of engineering design and investigate their conceptual connection to evolutionary biology. The basis for this work is an engineering design schema covering the central concepts of function, working principle and construction. Its relevance for evolutionary biology is explored by connecting these concepts to the so-called design space that is used in engineering optimisation. This tool makes it possible to distinguish various optima of performance and to visualise their robustness with respect to disturbances or changes in parameters. The robustness of morphological ‘constructions’ with regard to changes of shape is shown by means of examples from engineering and biology. The characteristics of various ‘landscapes’ in the design space is then related to the concept of evolvability, whereby we explore analogies between systems biology and morphology. A general property of phenotypes from the molecular to the organismal level seems to be that their ‘construction’ facilitates both their robustness and their exploration of the design space while maintaining the performance of the relevant functions at a high level.